Recreating Historic European Spindle Spinning - Mary Ann Megan Cleaton; Alice Rose Evans; Jane Hunt; Cathelina di Alessandri (EXARC Journal)
Spinning is a vital step in the production of textiles, whereby fibres are drawn out (drafted) and twisted together to make thread. In the present day, several culturally unique types of spinning are recognised, such as the thigh-rolling technique of traditional Navajo spinners who use unusually large spindles in a supported style (Wolf Creek, 2009). However, the default way of spinning with a spindle, particularly to Westerners, is usually considered to be “drop spinning”. Both modern recreationists and academics carrying out experimental archaeology typically either a) simply practice “drop spinning” without critically appraising their technique or b) consider the type(s) of spindle spinning practiced in Europe historically to be variant(s) of “drop spinning”. Additionally, they typically consider the distaff to be a flax-specific tool and often assert that wool was spun without a distaff. In contrast, we feel strongly that imagery showing European spindle spinning between circa 1100 and 1800 AD does not support these assertions. Additionally, we find that reproduction historical European spindles and whorls are poorly adapted for use with the “drop spinning” technique. These points led us to explore an alternative interpretation of the pictorial evidence and assess the practicality of this interpretation.